Pemanfaatan Sistem Informasi Manajemen Untuk Efisiensi Pengelolaan Usaha Mikro Kecil Dan Menengah (UMKM) - Fadillah, Siti Nur; Nasution, Muhammad Irwan Padli (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The development of information technology has significantly impacted the efficiency and effectiveness of Micro, Small, and Medium Enterprises (MSMEs) management. The utilization of Management Information Systems (MIS) assists MSME actors in managing business data more efficiently, quickly, and accurately. Through the implementation of MIS, activities such as financial recording, inventory management, and sales analysis can be automated, thereby supporting more accurate decision-making processes. This study aims to analyze how MIS implementation can improve operational efficiency and productivity among Indonesian MSMEs. The findings reveal that MIS adoption accelerates administrative processes, enhances data accuracy, and strengthens business competitiveness. However, challenges such as low digital literacy, infrastructure limitations, and implementation costs remain significant barriers. Therefore, collaboration between the government, business actors, and digital service providers is needed to optimize the adoption of MIS among MSMEs.